Aspirin relieves the calcification of aortic smooth muscle cells by enhancing the heat shock response - Quanquan Shen; Qian Chen; Yang Liu; Xiang Xue; Xiaogang Shen; Qiang He; Guokun Wang; Fei Han (Taylor & Francis Group, 2022)
Context Vascular calcification is a major complication of chronic renal failure, which has been identified as an active process partly driven by osteogenic transition of vascular smooth muscle cells (VSMCs). Aspirin could prevent cardiomyocyte damage by inducing heat shock response. Objective This study investigates the effect of aspirin on alleviating VSMC calcification. Materials and methods An in vitro VSMC calcification model was established by 10-day calcification induction in osteogenic medium. VSMCs were grouped as following: control group (normal medium), calcified group (osteogenic medium) and treated group (osteogenic medium with 1 or 4 mmol/L aspirin). VSMC calcification was evaluated by calcified nodules formation, intracellular calcium concentration and osteoblastic marker (OPN and Runx2) expression. Results After 10-day culture, the intracellular calcium concentration in calcified group was significantly higher than that in control group (1.16 ± 0.04 vs. 0.14 ± 0.01 μg/mg, p < 0.01), but significantly reduced in 1 mmol/L aspirin treated group (0.74 ± 0.05 μg/mg, p < 0.01), and 4 mmol/L aspirin treated group (0.93 ± 0.03 μg/mg, p < 0.01). The elevated expression of OPN and Runx2 induced by osteogenic medium was significantly relieved after 1 or 4 mmol/L aspirin treatment. The expression of HSF1, HSP70 and HSP90 was decreased in calcification-induced VSMCs, but significantly increased after treatment of aspirin. Furthermore, inhibition of HSP70 (or HSP90) by small-molecule inhibitor or small interfering RNA could partially abolish the anti-calcification effect of aspirin, proved by the changes of intracellular calcium concentration and osteoblastic marker expression. Discussion and conclusions Aspirin could relieve the calcification of VSMCs partially through HSP70- or HSP90-mediated heat shock response. These findings expanded the understanding of aspirin pharmacology, and imply that local induction expression of HSPs might be a potential therapeutic strategy for the prevention and therapy of vascular calcification.